A hemicyanine-based selective and sensitive colorimetric and fluorescent turn-on probe for Cu2+. Issue 48 (30th November 2016) - Zhu, Dongjian; Luo, Yanghe; Shuai, Liang; Xie, Wei; Yan, Xiaowei; Duan, Zhenhua; Cai, Wen
Graphical abstract: 2 can detect Cu 2+ over other metal ions by absorption spectra, fluorescence spectra and naked-eye. Highlights: A novel hemicyanine-based colorimetric and fluorescent turn-on probe2 for Cu 2+ was developed. The probe can detect Cu 2+ in the presence of 15 species of metal ions by absorption spectra, fluorescence spectra and naked-eye. The probe exhibited a rapid response of Cu 2+ within 72 s. The detection limit of2 for Cu 2+ was found to be 0.2 μM. Abstract: A hemicyanine-based colorimetric and fluorescent turn-on probe2 was designed and synthesized. The probe displayed a rapid response time, high sensitivity and high selectivity for Cu 2+ over other metal ions. Moreover, the probe can detect Cu 2+ in the presence of 15 species of metal ions by absorption spectra, fluorescence spectra and naked-eye in aqueous media.